Moderate Hypothermia Alleviates Sepsis-Associated Acute Lung Injury by Suppressing Ferroptosis Induced by Excessive Inflammation and Oxidative Stress via the Keap1/GSK3β/Nrf2/GPX4 Signaling Pathway - Xu J; Tao L; Jiang L; Lai J; Hu J; Tang Z (Dove Medical Press, 2024)
Jie Xu,1,2 Liujun Tao,1 Liangyan Jiang,1 Jie Lai,1 Juntao Hu,1 Zhanhong Tang1 1Department of Critical Care Medicine, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, 530021, People's Republic of China; 2Department of Critical Care Medicine, Suining Central Hospital, Suining, Sichuan, 629000, People's Republic of ChinaCorrespondence: Zhanhong Tang; Juntao Hu, Department of Critical Care Medicine, The First Affiliated Hospital of Guangxi Medical University, No. 6 Shuangyong Road, Nanning, Guangxi, 530021, Tel +86 13978816316 ; +86 18978866565, People's Republic of China, Email tangzhanhong139@sina.com; hujuntao80@126.comPurpose: Sepsis-associated acute lung injury (SA-ALI) is a common complication in patients with sepsis, contributing to high morbidity and mortality. Excessive inflammation and oxidative stress are crucial contributors to lung injury in sepsis. This study aims to examine the protective effects of moderate hypothermia on SA-ALI and explore the underlying mechanisms.Methods: Sepsis was induced in rats through cecal ligation and puncture followed by intervention with moderate hypothermia (32- 33.9°C). Blood, bronchoalveolar lavage fluid, and lung tissues were collected 12 hours post-surgery. Inflammatory responses, oxidative injury, SA-ALI-related pathophysiological processes, and Keap1/GSK3β/Nrf2/GPX4 signaling in septic rats were observed by ELISA, lung W/D ratio, immunohistochemistry, immunofluorescence, histological staining, Western blotting, RT-qPCR, and TEM assays.Results: Moderate hypothermia treatment alleviated lung injury in septic rats, reflected in amelioration of pathological changes in lung structure and improved pulmonary function. Further, moderate hypothermia reduced arterial blood lactate production and suppressed the expression of inflammatory factors IL-1β, IL-6, and TNF-α; downregulated ROS, MDA, and redox-active iron levels; and restored GSH and SOD content. TEM results demonstrated that moderate hypothermia could mitigate ferroptosis in PMVECs within lung tissue. The underlying mechanism may involve regulation of the Keap1/Nrf2/SLC7A11/GPX4 signaling pathway, with the insulin pathway PI3K/Akt/GSK3β also playing a partial role.Conclusion: Collectively, we illustrated a novel potential therapeutic mechanism in which moderate hypothermia could alleviate ferroptosis induced by excessive inflammation and oxidative stress via the regulation of Keap1/GSK3β/Nrf2/GPX4 expression, hence ameliorating acute lung injury in sepsis.Keywords: moderate hypothermia, sepsis, acute lung injury, ferroptosis, Nrf2, inflammation